PRINSIP-PRINSIP KESANTUNAN BERBAHASA DALAM INTERAKSI ANTARA SESAMA PENUTUR AMBON - Michele Hitijahubessy (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Language politeness plays a role in building good relations with someone because language politeness can make the interaction run smoothly, effectively, and not threatening face. Seeing this phenomenon researchers conducted research with the aim of describing the type of language principle in the interaction of Ambonese speakers. This study used qualitative methods with a pragmatic approach. In data collection, this study used three techniques, free speech techniques, recording techniques, and note-taking techniques. After the data was obtained, then the researcher clasified the data and then analyzed using the concepts of politeness principles from Leech (1983) and politeness strategies from Brown and Lavison (1987). The results of this study researchers found that Ambonese speakers interact daily using the six maxims: tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim. Politeness strategies used are positive politeness strategies and negative politeness strategies. This is so that the interaction can run smoothly, maintain good relations, and be effective.